Pelatihan Pemanfaatan Mobile Aplikasi Edmodo Pada Guru Seni Budaya - Agus Budiman; Heny Rohayani; Trianti Nugraheni (Mahesa Research Center, 2021)
The purpose of this study was to determine the results of online learning training for art teachers in Pandeglang-Banten through Edmodo Mobile-Application to be applied in art learning in schools. This qualitative study used a research sample of 40 training participants with a purposive sampling technique. The research data were obtained from the results of questionnaires and observations. The results showed that the mobile-application edomodo is one of the applications that can be accessed via smartphones or other technological devices such as laptops and computers, which can be used as a forum or means of art learning by both teachers and students through several features that can be used as access to learning media taught by students and teachers. The results of this training are able to improve the pedagogical ability and professionalism of teachers in implementing technology-based art learning. The conclusion of this study is that the skills of teachers in using technology in art learning in the industrial era 4.0 need to be improved as an effort to adapt to various technological and information developments that must be utilized in art education.